Optimized Synthesis of Small and Stable Silver Nanoparticles Using Intracellular and Extracellular Components of Fungi: An Alternative for Bacterial Inhibition - Elvira Ivonne Murillo-Rábago; Alfredo R. Vilchis-Nestor; Karla Juarez-Moreno; Luis E. Garcia-Marin; Katrin Quester; Ernestina Castro-Longoria (MDPI AG, 2022)
Silver nanoparticles (AgNPs) represent an excellent option to solve microbial resistance problems to traditionally used antibiotics. In this work, we report optimized protocols for the production of AgNPs using extracts and supernatants of Trichoderma harzianum and Ganoderma sessile. AgNPs were characterized using UV-Vis spectroscopy and transmission electron microscopy, and the hydrodynamic diameter and Z potential were also determined. The obtained AgNPs were slightly larger using the fungal extract, and in all cases, a quasi-spherical shape was obtained. The mean sizes of AgNPs were 9.6 and 19.1 nm for T. harzianum and 5.4 and 8.9 nm for G. sessile using supernatant and extract, respectively. The AgNPs were evaluated to determine their in vitro antibacterial effect against Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus. The minimum inhibitory concentration (MIC) was determined, and in all cases the AgNPs showed an antimicrobial effect, with a MIC varying from 1.26-5.0 µg/mL, depending on the bacterial strain and type of nanoparticle used. Cytotoxicity analyses of AgNPs were carried out using macrophages and fibroblast cell lines. It was determined that the cell viability of fibroblasts exposed for 24 h to different concentrations of AgNPs was more than 50%, even at concentrations of up to 20 µg/mL of silver. However, macrophages were more susceptible to exposure at higher concentrations of AgNPs as their viability decreased at concentrations of 10 µg/mL. The results presented here demonstrate that small AgNPs are obtained using either supernatants or extracts of both fungal strains. A remarkable result is that very low concentrations of AgNPs were necessary for bacterial inhibition. Furthermore, AgNPs were stable for more than a year, preserving their antibacterial properties. Therefore, the reported optimized protocol using fungal supernatants or extracts may be used as a fast method for synthesizing small AgNPs with high potential to use in the clinic.